2022
DOI: 10.7717/peerj.13562
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection plays a significant role in governing the codon usage bias in the novel SARS-CoV-2 variants of concern (VOC)

Abstract: The ongoing prevailing COVID-19 pandemic caused by SARS-CoV-2 is becoming one of the major global health concerns worldwide. The SARS-CoV-2 genome encodes spike (S) glycoprotein that plays a very crucial role in viral entry into the host cell via binding of its receptor binding domain (RBD) to the host angiotensin converting enzyme 2 (ACE2) receptor. The continuously evolving SARS-CoV-2 genome results in more severe and transmissible variants characterized by the emergence of novel mutations called ‘variants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…The results (Fig. 2 D) showed that most of the SARS-CoV-2 isolates gave values slightly below the standard curve (R 2 = 0.7562, P = 0.0023), indicating that the codon usage bias was affected by both mutation pressure and evolutionary pressure, consistent with previous reports [ 30 , 31 ]. Neutrality plot analysis showed that the linear regression coefficient of SARS-CoV-2 sequences was -0.1156 (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The results (Fig. 2 D) showed that most of the SARS-CoV-2 isolates gave values slightly below the standard curve (R 2 = 0.7562, P = 0.0023), indicating that the codon usage bias was affected by both mutation pressure and evolutionary pressure, consistent with previous reports [ 30 , 31 ]. Neutrality plot analysis showed that the linear regression coefficient of SARS-CoV-2 sequences was -0.1156 (Fig.…”
Section: Resultssupporting
confidence: 90%
“…This result indicates that G+C composition is the dominant factor of SARS-CoV-2’s codon usage, but nature selection also affects SARS-CoV-2’s codon usage. Natural selection may play more important roles in some genes than the genome level (S gene, for example) ( Posani et al, 2022 ; Tyagi et al, 2022 ). The average codon adaptation index (CAI) of all strains at the genome level is 0.7200.…”
Section: Resultsmentioning
confidence: 99%
“…When the coefficient of GC3 approaches 1, mutational pressure predominantly governs codon usage 33,34 . Conversely, a slope nearing 0 indicates a diminishing impact of mutational pressure, implying a stronger influence of natural selection 35,36 . In this study, analysis of the neutrality plot (Figure 2) revealed a modest yet statistically significant positive correlation between GC12 and GC3, as indicated by the regression equation 𝑦 = 0.388 + 0.165𝑥; 𝑅2 = 0.14; 𝑝 < 0.001.…”
Section: Neutrality Plot Analysismentioning
confidence: 99%